CLIMATE-SMART AGRIBUSINESS STRATEGIES FOR SMALLHOLDER FARMERS IN EMERGING ECONOMIES - Lituhayu Supartiningrum (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2026)
This study aims to analyze various climate-smart agriculture-based agribusiness strategies that can be implemented by smallholder farmers to address the challenges of climate change in developing countries. The research method used was a literature review, examining various scientific articles, books, international reports, and previous research results relevant to the theme of climate-smart agribusiness. Data were analyzed descriptively and comparatively to identify effective strategies for increasing productivity, adaptation, and sustainability of farming businesses. The study results indicate that climate-smart agribusiness strategies include farm diversification, the use of digital agricultural technology, the implementation of water-efficient irrigation, the use of climate-resilient varieties, agroforestry, and strengthening market access and green financing. Furthermore, collaboration between governments, financial institutions, the private sector, and local communities is a crucial factor in supporting the successful implementation of these strategies. A climate-smart agribusiness approach can not only increase agricultural productivity but also strengthen the economic resilience of smallholder farmers to the risks of climate change. This study emphasizes that sustainability-based agribusiness transformation needs to be supported through inclusive policies, technological innovation, and farmer capacity building to create adaptive, resilient, and sustainable agricultural systems in developing countries.